Reducing Pesticide Risk Associated With Dollar Spot Management on Golf Course Turfgrass - Bekken, Michael A. H.; Hockemeyer, Kurt R.; Soldat, Douglas J.; Koch, Paul L. (Frontiers in Agronomy, 2022)
Pesticides are critical tools for golf course managers to maintain healthy and economically profitable golf course playing surfaces. However, the intensity and types of pesticides used on golf courses can be harmful to human and environmental health. Two separate studies were conducted at two locations in Wisconsin, USA between 2014 and 2020 to test the ability of reduced risk fungicide programs to control dollar spot (Clarireedia spp.) on golf course fairways and putting greens. Risk of the pesticide application programs was quantified in both studies using the active ingredient application rate, the Environmental Impact Quotient (EIQ), hazard quotient (HQ), and the Pesticide Risk Tool (PRT). The first study found that using the Smith-Kerns Dollar Spot Prediction Model to schedule fungicide applications did not reduce pesticide risk on its own, but that a pesticide program utilizing reduced risk products was just as effective in controlling dollar spot as a conventional program while reducing pesticide risk by approximately 50 to 80% depending on the pesticide risk indicator used. The second study established an average pesticide risk using HQ based on the pesticide records of 23 randomly selected Wisconsin golf courses. This statewide average was then used to test pesticide programs at 100, 75, 50, and 25% of the average risk for their efficacy in controlling dollar spot over a 4-year period. In the 4 years of the study, dollar spot severity of the 25% risk treatment was statistically indistinguishable from the other three programs. Taken together, these results indicate that pesticide risk can be significantly reduced on golf courses in the US Midwest without sacrificing dollar spot control.